Misty Hyman's Turn-kick at 150 m of Her 200 m Butterfly Bronze Medal Race at the 1997 Pan Pacific Championships, Fukuoka, Japan - Rushall, B. S. (1999)
Video pictures (16 frames) and the appropriate technical/ biomechanical explanations for Misty Hyman's Turn-kick at 150 m of Her 200 m Butterfly Bronze Medal Race at the 1997 Pan Pacific Championships, Fukuoka, Japan. This sequence illustrates the following phenomena: 1.Misty Hyman never achieves the position that is normally described for her or illustrated in the above photos. 2.The change from flat to incline and back again is not smooth. This suggests that for an underwater double-leg kick, rolling onto the side is difficult to achieve. It is quite possible that it is against the forces of better hydrodynamics. 3.The swimmer takes longer (2.6 seconds) to attain maximum rotation (53 degrees) than to return to flat (1.33 seconds). This too suggests that rotating while doing a double-leg kick is difficult for this swimmer. 4.At no time is the swimmer stable and on her side. She is either flat or rolling.